2015
DOI: 10.1021/acscatal.5b00402
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Reduction of CO2 on Tin Electrodes using in Situ ATR-IR Spectroscopy

Abstract: The reduction of CO2 on tin cathodes was studied using in situ attenuated total reflectance infrared spectroscopy (ATR-IR). Thin films of a mixed Sn/SnO x species were deposited onto a single-crystal ZnSe ATR crystal. Peaks centered at about 1500, 1385, and 1100 cm–1, attributed to a surface-bound monodentate tin carbonate species, were consistently present under conditions at which CO2 reduction takes place. It was shown that these peaks are only present at potentials where CO2 reduction is observed. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
437
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 444 publications
(477 citation statements)
references
References 37 publications
32
437
1
7
Order By: Relevance
“…This problem has been neglected for the study of CO 2 reduction until Chen et al reported their experiments [23]. Baruch et al studied the electrochemical reduction of CO 2 on Sn cathode by utilizing in situ attenuated total reflectance infrared spectroscopy, and found that the peaks attributed to a surface-bound monodentate tin carbonate species (intermediate of CO 2 reduction) only appeared at potentials where CO 2 reduction was observed, and disappeared when the tin surface was chemically etched to remove surface oxide [24]. In this work, the CV and the electrolysis results illustrate that Sn electrode possessing oxide layer shows excellent catalytic activity for CO 2 reduction, and the Sn electrode removed its oxide layer shows poor catalytic activity for CO 2 reduction but hydrogen evolution reaction accelerates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem has been neglected for the study of CO 2 reduction until Chen et al reported their experiments [23]. Baruch et al studied the electrochemical reduction of CO 2 on Sn cathode by utilizing in situ attenuated total reflectance infrared spectroscopy, and found that the peaks attributed to a surface-bound monodentate tin carbonate species (intermediate of CO 2 reduction) only appeared at potentials where CO 2 reduction was observed, and disappeared when the tin surface was chemically etched to remove surface oxide [24]. In this work, the CV and the electrolysis results illustrate that Sn electrode possessing oxide layer shows excellent catalytic activity for CO 2 reduction, and the Sn electrode removed its oxide layer shows poor catalytic activity for CO 2 reduction but hydrogen evolution reaction accelerates.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al reported that Sn/SnO x layer on Ti substrate is highly selective towards CO and HCOOH compared to pure Sn, and they obtained the highest faradaic efficiency of 95% for CO 2 reduction (40% for producing formate and 55% for producing CO) at −0.7 V vs. RHE [23]. Baruch et al studied the electrochemical reduction of CO 2 on Sn cathode and reported that a metastable oxide layer presented on the surface of the Sn cathode under reducing potentials [24].…”
Section: Introductionmentioning
confidence: 99%
“…SnO 2 /C has low H 2 production (metal with high hydrogen overpotential), and catalyzes the CO 2 electrochemical reduction to CO (Figure 7e). Actually, previously published works have found that, even at negative potentials, tin may exist as tin hydroxide 69 and the main product of the CO 2 electroreduction is formate ions, 14 being CO a parallel or secondary product (formate cannot be detected be DEMS). So, part of the electrochemical current for SnO 2 /C observed in Figure 7a is spent in the production of formate ions, which is not counted in the present study, explaining the lowest ionic currents for CO and H 2 .…”
Section: Electrochemical Experiments Electrocatalytic Reduction Of Comentioning
confidence: 99%
“…Studies on tin 5,6 and indium 7,8 have demonstrated the importance of a hydrated oxide layer, either native or anodized, which can interact with CO 2 to form a surface-bound carbonate species that is implicated as an essential intermediate. Other research has shown that a size-dependence exists on gold, 9,10 palladium, 11 silver, 10,12,13 and tin oxide 14 nanoparticles for the conversion of CO 2 , with an optimum diameter less than 10 nm but typically greater than 2 nm.…”
mentioning
confidence: 99%